The Hadiths on Rising for Funeral among the Hadith Scholars and Jurists (Fuqaha) An Applied Study from the Book (Sunna Abo Dawood) - Abuftaim, Abdullah Salem (Journal of Islamic Sciences, 2024)
The research examines the hadiths mentioned by Imam Abu Dawood Suleiman bin Al-Ash'ath Al-Sijistani in his book "Sunan" regarding the issue of standing up for the funeral procession. The researcher studied these hadiths both in terms of their authenticity and legal implications.The aim of the research was to clarify the need for differing opinions on the issue of standing up for the funeral procession, studying the apparent contradictions in the hadiths concerning standing for it, and mentioning the differences in the case of the follower of the funeral procession and the one sitting when it passes by. It also aimed to explain the reason for standing for the funeral procession upon which the ruling was based, and to clarify the legal ruling on it.One of the results of the researcher's study is the consideration of the issue of standing for the funeral as a matter that justifies the difference in its ruling. The reason is the contradiction in the apparent evidence, and what has come from the hadiths indicating sitting, as practiced by the Prophet (peace be upon him), and his opposition to the Jews in what they used to do in standing for the funerals. It is preferable to say that standing for the funeral is absolutely disliked, and for those walking behind the funeral, it is disliked for them to sit until it is placed on the ground from the shoulders.
Keywords: standing for the funeral; funeral; death; funeral procession; passing by the funeral; mourners